Hubungan Perilaku Makan dan Aktifitas Fisik dengan Status Gizi Anak Usia Sekolah - Purnama, Ni Luh Agustini; Sinawang, Gabriel Wanda; Ekawati, Nora (Universitas Malahayati, 2024)
ABSTRACT Children's eating behavior can influence the adequacy of their food intake, which will have an impact on nutritional status. Apart from eating behavior, physical activity also influences the nutritional status of school children. The physical activity of school children is something that must be considered because school-aged children experience rapid growth and development and can change their physical condition. The purpose of this study is to determine the connection between school-aged children's eating habits, physical activity, and nutritional status. A cross-sectional research design was used. The research subjects were 36 students at SD Pakis Gelora Surabaya who met the inclusion criteria. The Children's Eating Behavior Questionnairec (CEBQ) was used to measure eating behavior. With the help of the Physical Activity Questionnaire for Children (PAQ-C), physical activity was assessed. Status assessment used the BMI/U Z-score indicator. The results of the Spearman Rank analysis showed that there was a moderately strong positive correlation between eating behavior and the nutritional status of school-age children (p=0.0001, correlation coefficient=0.634). Physical activity and nutritional status were significantly negatively related (p= 0.001 correlation coefficient -0.523). It can be concluded that children who increasingly like to eat have an increasing nutritional status and vice versa, children who do not like eating have an increasingly decreasing nutritional status. The more physical activity a child increases, the more their nutritional status decreases, and vice versa, children who do not do much physical activity have an increasing nutritional status. Keywords: Eating Behavior, Physical Activity, Nutritional Status, School Age ABSTRAK Perilaku makan dapat memengaruhi kecukupan asupan nutrisi yang berdampak terhadap kondisi gizi anak. Selain perilaku makan aktifitas fisik juga memengaruhi kondisi gizi anak sekolah. Aktifitas fisik anak sekolah adalah hal yang harus diperhatikan karena terjadi pertumbuhan dan perkembangan yang cepat pada anak sekolah yang berdampak pada perubahan kondisi fisik. Tujuan dari penelitian ini adalah mengidentifikasi hubungan antara perilaku makan, aktifitas fisik dengan status gizi anak usia sekolah. Penelitian ini adalah penelitian cross sectional. Subjek penelitian sebanyak 36 siswa di SD Pakis Gelora Surabaya yang memenuhi kriteria inklusi. Perilaku makan diukur dengan menggunakan Children’s Eating Behavior Questionnaire (CEBQ. Aktifitas fisik diukur menggunakan instrumen Physical Activity Questionnaire For Children (PAQ-C). Penilaian status menggunakan indikator Z-skor IMT/U. Hasil analisis Rank Spearman menunjukkan terdapat korelasi yang signifikat positif dengan kekuatan sedang perilaku makan dengan status gizi anak usia sekolah (p=0.0001, koefisen korelasi=0.634). Aktifitas fisik dan status gizi signifikan berhubungan negative (p= 0.001 koefisen korelasi -0.523). Dapat disimpulkan bahwa anak yang semakin suka makan memiliki status gizi yang semakin meningkat begitu pula sebaliknya anak yang tidak suka makan memiliki status gizi yang semakin menurun. Semakin meningkat aktifitas fisik yang dilakukan anak semakin menurun status gizinya begitu pula sebaliknya anak yang tidak banyak melalakukan aktifitas fisik memiliki status gizi yang semakin meningkat Kata Kunci: Perilaku Makan, Aktifitas Fisik, Status Gizi, Usia Sekolah